The Routledge Companion to Rehabilitative Work in Criminal Justice - Ugwudike, Pamela (Routledge, 2019)
Cover -- Half Title -- Title -- Copyright -- Contents -- Preface -- List of figures -- List of tables -- List of contributors -- 1 An introduction to The Routledge Companion to Rehabilitative Work in Criminal Justice -- Section 1: Theories and models for working with offenders -- 2 Conceptualizing rehabilitation: four forms, two models, one process, and a plethora of challenges -- 3 Promoting inclusion and citizenship?: selective reflections on the recent history of the policy and practice of rehabilitation in England and Wales -- 4 Should there be a right to rehabilitation? -- 5 Human rights and rehabilitative work in criminal justice -- 6 Retribution and rehabilitation: taking punishment seriously in a humane society -- 7 Restorative justice: a different approach to working with offenders and with those whom they have harmed -- 8 The evidence-based approach to correctional rehabilitation: current status of the Risk-Need- Responsivity (RNR) model of offender rehabilitation -- 9 An overview of the Good Lives Model: theory and evidence -- 10 Diversifying desistance research -- 11 Doing justice to desistance narratives -- 12 Therapeutic justice and rehabilitation -- Section 2: Policy contexts and cultures -- 13 The 'Transforming Rehabilitation' agenda in England and Wales: implications of privatization -- 14 The rehabilitative prison: an oxymoron, or an opportunity to radically reform the way we do punishment? -- 15 Rehabilitation and re-entry in Scandinavia -- 16 Using technology and digitally enabled approaches to support desistance -- 17 Prisons, personal development, and austerity -- Section 3: Assessment practice -- 18 Risk and need assessment: development, critics, and a realist approach.